Competitiveness and Market Concentration of Islamic Banking Industry: A Comparison Study between Indonesia and Malaysia - Helma Malini; Alifah Nurrahmani Putri (Faculty of Economics, Universitas Sriwijaya, 2020)
Financial integration in the ASEAN Economic community (AEC) by 2020 forces Islamic banks in Indonesia and Malaysia to be more competitive and have market power domestically and internationally to ensure business sustainability and increase assets rapidly in order to boost market share of Islamic banking in Indonesia and Malaysia. Islamic bank market competitiveness and power will determine the returns, investment, asset and trust of Islamic banks. The study uses data from 10 Islamic banks in Indonesia and Malaysia. The result confirmed that Islamic banking in Indonesia are characterized by the monopolize industry and Islamic bank in Malaysia are characterized by oligopoly Industry.